Algunas observaciones sobre el estudio de la historia cultural del esoterismo occidental en América Latina - Bubello, Juan Pablo (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2020)
In the early 1990s, Western esotericism became an academic subject within the realm of history. Thanks to a plethora of research, our field has grown twofold via the emergence of a solid specialized journals; and of three large networks of specialists (the Association for the Study of Esotericism-ASE; the European Society for the Study of Western Esotericism-ESSWE, and Centro de Estudios sobre el Esoterismo Occidental/UNASUR). Even though the history of western esotericism in Latin America has yet to be written, there are some methodological preventions to point out that every specialist in Esoterism should observe.